Transcriptional Control of Quality Differences in the Lipid-Based Cuticle Barrier in Drosophila suzukii and Drosophila melanogaster - Wang, Yiwen; Farine, Jean-Pierre; Yang, Yang; Yang, Jing; Tang, Weina; Gehring, Nicole; Ferveur, Jean-François; Moussian, Bernard (Frontiers in Genetics, 2020)
The fruit flies Drosophila suzukii and Drosophila melanogaster live on fruits. They have, however, developed different life strategies. While D. suzukii prefers ripening fruits, D. melanogaster lives on rotten fruits. These preferences may correlate with the microclimate especially humidity conditions of their habitats. Here, we asked whether the dissimilar lifestyles entail differences in cuticle barrier function in these species. In particular, we compared the basic properties of the cuticle inward and outward barrier function in adults of these species under the same laboratory conditions. At low air humidity, D. suzukii flies desiccate faster than D. melanogaster flies. We observed a general trend indicating that in this respect males are less robust than females in both species. Xenobiotics penetration occurs at lower temperatures in D. suzukii than in D. melanogaster. Likewise, D. suzukii flies are more susceptible to contact insecticides than D. melanogaster flies. Thus, both the inward and outward barriers of D. suzukii are less efficient. Consistently, D. suzukii flies have less cuticular hydrocarbons (CHC) that participate as key components of the cuticle barrier. Especially, the relative amounts of branched and desaturated CHCs, known to enhance desiccation resistance, show reduced levels in D. suzukii. Moreover, the expression of snustorr (snu) that encodes an ABC transporter involved in barrier construction and CHC externalization, is strongly suppressed in D. suzukii. Hence, species-specific genetic programs regulate the quality of the lipid-based cuticle barrier in these two Drosophilae. Together, we conclude that the weaker inward and outward barriers of D. suzukii may be partly explained by differences in CHC composition and by a reduced Snu-dependent transport rate of CHCs to the surface.